Bihar Second Five-Year Plan - Planning Commission (Planning Commission, 1956)
The Constitution lays down the goal for the country. The directive principled of State policy which govern both the State and the Central Governments require that their activity should be directed to promote the welfare of the people by securing and protecting, as effectively as they may, a social order in which justice, social, economic and political shall inform all the institutions of the national life.
Bihar